A qualitative descriptive analysis of effects of psychedelic phenethylamines and tryptamines. (7th January 2020) - Palamar, Joseph J.; Acosta, Patricia
Abstract: Objective: The number of novel psychedelic phenethylamines and tryptamines has continued to increase, but little academic research has focused on the effects of these substances. We sought to determine and compare the subjective effects of various substances. Methods: We conducted in‐depth interviews with 39 adults (75.4% male and 87.2% White) who reported experience using psychedelic phenethylamines and/or tryptamines. Participants described the effects of compounds they have used. We examined the subjective drug effects in a qualitative descriptive manner. Results: Participants reported on the use of 36 compounds. The majority (64.1%) reported the use of 2C series drugs, with 2C‐B use being most prevalent; 38.5% reported the use of NBOMe, and 25.6% reported the use of DOx. With regard to tryptamines, 46.2% reported use, and 4‐AcO‐DMT was the most prevalent drug used in this class. 2C‐B was often described as being more favorable than other 2C series compounds with the effects described as being comparable with MDMA and LSD. NBOMe effects were generally described in an unfavorable manner, and the effects of DOx were often described as lasting too long (12–36 hr). The effects of 4‐AcO‐DMT were often described as mimicking psilocybin. Conclusion: Knowing the effects of various compounds can inform education, prevention, and harm reduction efforts regarding the use of these drugs.